2012
DOI: 10.1063/1.4711396
|View full text |Cite
|
Sign up to set email alerts
|

Mixing properties of coaxial jets with large velocity ratios and large inverse density ratios

Abstract: An experimental study was conducted to better understand the mixing properties of coaxial jets as several parameters were systematically varied, including the velocity ratio, density ratio, and the Reynolds number. Diameters of the inner and outer jet were also varied. Coaxial jets are commonly used to mix fluids due to the simplicity of their geometry and the rapid mixing that they provide. A measure of the overall mixing efficiency is the stoichiometric mixing length (Ls), which is the distance along the jet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…The stability characteristics of coaxial jets are not only important for bypass jet engines but also for many other devices in which dual-stream nozzles are used to mix different fluids. 4 The mixing properties of the two streams depend significantly on the disturbance development within the inner and outer shear layer of the coaxial jet flow.…”
Section: Introductionmentioning
confidence: 99%
“…The stability characteristics of coaxial jets are not only important for bypass jet engines but also for many other devices in which dual-stream nozzles are used to mix different fluids. 4 The mixing properties of the two streams depend significantly on the disturbance development within the inner and outer shear layer of the coaxial jet flow.…”
Section: Introductionmentioning
confidence: 99%
“…With the progress of technology [23], it is found that the properties of breakup morphology and fragment distribution in different regimes are different [24][25][26][27][28]. Coaxial air-blast atomizers have many applications [29][30][31]. In order to obtain the desired results of atomization in the industrial scale, the suitable range of nozzle size and operating condition could be determined with the help of the regime map.…”
Section: Primary Atomizationmentioning
confidence: 99%
“…For an inviscid ideal gas, substituting Equations (1), (4) and 6into Equations 7and 8, the continuity equation is expressed as:…”
Section: Governing Equationmentioning
confidence: 99%
“…Similarly, substituting Equations (1), (4) and 6into Equations 7and 8, and neglecting the nonlinear terms of the disturbance, the momentum equation is obtained as follows:…”
Section: Governing Equationmentioning
confidence: 99%
See 1 more Smart Citation